Clustering-based enhanced safety message dissemination medium access control protocol for vehicular ad hoc network. (2017) - Gupta, Nishu; Prakash, Arun; Tripathi, Rajeev
Wireless access in vehicular environment employs the IEEE 802.11p/1609.4 standard wherein a multichannel architecture is envisioned to concurrently support both time-sensitive safety-related applications and value-added entertainment services. Although a standard now, the IEEE 802.11p protocol has known shortcomings of not being capable of providing reliable broadcast services. To address this issue, clustering-based enhanced safety message dissemination MAC protocol (CESD-MAC) is proposed in this paper which is an enhancement over the existing IEEE 802.11p/1609.4 protocol. CESD-MAC adopts mobility aware clustering and channel access scheduling. It rules out the concept of switching between the control channel and the service channel as implemented in the legacy standard. Simulation results are presented to verify the effectiveness of the proposed protocol and comparisons are made with the existing IEEE 802.11p MAC. The results demonstrate the superiority of CESD-MAC in terms of reduction of end-to-end delay, and increased throughput, channel utilisation and packet delivery ratio (PDR).